Non-Hodgkin's lymphoma in systemic lupus erythematosus. Issue 10 (14th September 2005) - Bernatsky, S; Ramsey-Goldman, R; Rajan, R; Boivin, J-F; Joseph, L; Lachance, S; Cournoyer, D; Zoma, A; Manzi, S; Ginzler, E; Urowitz, M; Gladman, D; et al.
Abstract : Background: Recent evidence supports an association between systemic lupus erythematosus (SLE) and non-Hodgkin's lymphoma (NHL). Objectives: To describe demographic factors, subtypes, and survival of patients with SLE who develop NHL. Methods: A multi-site cohort of 9547 subjects with definite SLE was assembled. Subjects at each centre were linked to regional tumour registries to determine cancer cases occurring after SLE diagnosis. For the NHL cases ascertained, descriptive statistics were calculated, and NHL subtype frequency and median survival time of patients determined. Results: 42 cases of NHL occurred in the patients with SLE during the 76 948 patient-years of observation. The median age of patients at NHL diagnosis was 57 years. Thirty six (86%) of the 42 patients developing NHL were women, reflecting the female predominance of the cohort. In the patients, aggressive histological subtypes appeared to predominate, with the most commonly identified NHL subtype being diffuse large B cell (11 out of 21 cases for which histological subtype was available). Twenty two of the patients had died a median of 1.2 years after lymphoma diagnosis. Conclusions: These data suggest aggressive disease in patients with SLE who develop NHL. Continuing work should provide further insight into the patterns of presentation, prognosis, and aetiology of NHL in SLE.